Multiple-Knapsack Optimization in Land Conservation: Results from the First Cost-effective Conservation Program in the United States. - Messer, Kent D.; Kecinski, Maik; Xing Tang; Hirsch IV, Robert H. (Land Economics, 2016)
Conservation groups often piece together their parcel selections by combining funds from multiple sources. When applying multiple-knapsack optimization, substantial increases in conservation benefits, acreage, and number of parcels preserved can be achieved. Specifically, we show that multiple-knapsack optimization substantially outperforms benefit targeting, cost-effectiveness analysis, and sequential binary integer programming. This study uses data from the first known cost-effective land conservation program in the United States--in Baltimore County, Maryland--and shows that multiple- knapsack optimization can deliver additional benefits.